Mechanically tunable coaxial electrospun models of YAP/TAZ mechanoresponse and IGF-1R activation in osteosarcoma. (December 2019) - Molina, Eric R.; Chim, Letitia K.; Salazar, Maria C.; Mehta, Shail M.; Menegaz, Brian A.; Lamhamedi-Cherradi, Salah-Eddine; Satish, Tejus; Mohiuddin, Sana; McCall, David; Zaske, Ana Maria; Cuglievan, Branko; Lazar, Alexander J.; et al.
Abstract: Current in vitro methods for assessing cancer biology and therapeutic response rely heavily on monolayer cell culture on hard, plastic surfaces that do not recapitulate essential elements of the tumor microenvironment. While a host of tumor models exist, most are not engineered to control the physical properties of the microenvironment and thus may not reflect the effects of mechanotransduction on tumor biology. Utilizing coaxial electrospinning, we developed three-dimensional (3D) tumor models with tunable mechanical properties in order to elucidate the effects of substrate stiffness and tissue architecture in osteosarcoma. Mechanical properties of coaxial electrospun meshes were characterized with a series of macroscale testing with uniaxial tensile testing and microscale testing utilizing atomic force microscopy on single fibers. Calculated moduli in our models ranged over three orders of magnitude in both macroscale and microscale testing. Osteosarcoma cells responded to decreasing substrate stiffness in 3D environments by increasing nuclear localization of Hippo pathway effectors, YAP and TAZ, while downregulating total YAP. Additionally, a downregulation of the IGF-1R/mTOR axis, the target of recent clinical trials in sarcoma, was observed in 3D models and heralded increased resistance to combination chemotherapy and IGF-1R/mTOR targeted agents compared to monolayer controls. In this study, we highlight the necessity of incorporating mechanical cues in cancer biology investigation and the complexity in mechanotransduction as a confluence of stiffness and culture architecture. Our models provide a versatile, mechanically variable substrate on which to study the effects of physical cues on the pathogenesis of tumors. Statement of significance: The tumor microenvironment plays a critical role in cancer pathogenesis. In this work, we engineered 3D, mechanically tunable, coaxial electrospun environments to determine the roles of the mechanical environment on osteosarcoma cell phenotype, morphology, and therapeutic response. We characterize the effects of varying macroscale and microscale stiffnesses in 3D environments on the localization and expression of the mechanoresponsive proteins, YAP and TAZ, and evaluate IGF-1R/mTOR pathway activation, a target of recent clinical trials in sarcoma. Increased nuclear YAP/TAZ was observed as stiffness in 3D was decreased. Downregulation of the IGF-1R/mTOR cascade in all 3D environments was observed. Our study highlights the complexity of mechanotransduction in 3D culture and represents a step towards controlling microenvironmental elements in in vitro cancer investigations. Graphical abstract: Image, graphical abstract